Respuesta :

the answer is basically A

we are given

[tex]y=cos(2x)[/tex]

Since, we have to find inverse function

so, we will use following steps

step-1:

Set y=f(x)

It is already there

step-2:

Switch x and y

[tex]x=cos(2y)[/tex]

step-3:

Solve for y

[tex]x=cos(2y)[/tex]

we can take cos^-1 both sides

[tex]cos^{-1}(x)=cos^{-1}(cos(2y))[/tex]

now, we can simplify it

[tex]cos^{-1}(x)=2y[/tex]

Divide both sides by 2

[tex]y=\frac{cos^{-1}(x)}{2}[/tex]

so, option-D........Answer

ACCESS MORE